ANALISIS KOMPREHENSIF TEORI DAN PRAKTIK EVALUASI KURIKULUM - Muhammad Arif Pahsa Al Muttaqin; Haidar Hafiedz; Muh Agus Syahnginata Surya; Eko Nursalim (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Curriculum evaluation is a crucial instrument in ensuring the quality and relevance of education in response to global developments. This article aims to comprehensively examine the basic concepts, theoretical models, and implementation mechanisms of curriculum evaluation within educational institutions. Using a literature review method, the discussion begins by defining curriculum evaluation as a systematic process of gathering and analyzing information for decision-making. Furthermore, various popular evaluation models, such as the CIPP model, Tyler’s model, and Goal-Free Evaluation, are presented along with their specific characteristics. In the final section, this article outlines the stages of evaluation implementation, covering planning, data collection, and follow-up actions based on evaluation results. The findings of this study are expected to provide a framework for educational practitioners to conduct continuous, data-driven curriculum improvements.